MUMTOZ ADABIY MATN LEKSIKASINI O‘RGANISHNING ZAMONAVIY LINGVISTIK YONDASHUVLARI (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article examines modern linguistic approaches to the study of lexical features in classical literary texts. Classical literature represents an important source of the lexical richness of the Uzbek language and reflects the cultural and historical heritage of the nation. The study of the vocabulary used in classical literary texts is significant for linguistics, literary studies, and cultural studies. The article discusses modern linguistic methods used in analyzing classical texts, including semantic analysis, linguocultural approaches, corpus linguistics, and discourse analysis. Particular attention is given to archaic vocabulary, historical lexical units, and their relationship with modern language usage. The research findings demonstrate that modern linguistic approaches allow for a deeper understanding of lexical structures in classical texts and reveal their role in the development of language and culture.